AB0181 Diffusing capacity and clinical characteristics of patients with systemic sclerosis – data from the german network for systemic sclerosis. (15th June 2017) - Moinzadeh, P; Blank, N; Siegert, E; Henes, J; Worm, M; Sunderkoetter, C; Schmalzing, M; Kreuter, A; Gunther, C; Susok, L; Zeidler, G; Koetter, I; et al.
Abstract : Background: Lung involvement, i.e. interstitial lung disease (ILD) and pulmonary hypertension (PH), is common in patients with systemic sclerosis (SSc), significantly limiting quality of life and survival. Data on clinical correlations between lung function and clinical subsets of SSc are sparse. Objectives: To investigate the relationship of DLCO and clinical characteristics in patients SSc patients within the registry of the German Network for Systemic Scleroderma. Methods: Clinical data of the patient registry, currently including DLCO data of 1917 patients were evaluated. In total, these patients were clinically evaluated 5997 times (i.e., at the first visit and during follow-up visits). At the initial visit and during follow-up DLCO levels were correlated with clinical characteristics. Results: At initial presentation, 64% of the patients had DLCO levels <75% predicted. Impaired DLCO levels were observed in 74% of dcSSc patients, in 64% of SSc-Overlap patients and 57% of lcSSc patients (p<0.0001). Furthermore, male patients (62%), patients with PH (80%), ILD (80%), dyspnea (78%), and those with presence of anti-topoisomerase I antibodies (71%) exhibited significantly more often DLCO levels <75% (p<0.01). Patients suffering from dcSSc had the lowest DLCO levels (mean value, 62%), followed by patients with SSc-Overlap syndromes (mean value, 67%) and lcSSc patients (mean value, 70%) revealing significant differences between subsets. Long-term follow-up evaluation (mean follow up, 6.0 years) revealed that in comparison to lcSSc patients dcSSc patients (OR 2.1; p<0.0001; 95%>CI 1.7–2.5) and SSc-Overlap patients (OR, 1.55; p<0.0001; 95% CI, 1.2–2.0) had a significantly increased risk to a decrease in DLCO levels <75%. Conclusions: Impairment of pulmonary function as determined by diffusing capacity DLCO is more common and more pronounced in patients with dcSSc and SSc-Overlap Syndrome compared to lcSSc. DLCO may be useful for diagnosing and monitoring pulmonary involvement in SSc. Disclosure of Interest: None declared